2016
DOI: 10.17576/3l-2016-2201-04
|View full text |Cite
|
Sign up to set email alerts
|

Regularities and Irregularities in Rhetorical Move Structure of Linguistics Abstracts in Research Articles

Abstract: Awareness of abstract writing skill plays an important role for research article (RA) abstract writers to meet the discourse community expectations.In academic writing, writers should persuade readers to read the whole article by writing an effective abstract in terms of both content and rhetorical structure. This paper utilised Swales ' (1990)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…In this light, prior research claims that rhetorical styles of particular genres are worth exploring in the English as Academic Purposes (EAP) class (Loi et al, 2015). It is also essential to introduce the concept of rhetorical styles in the academic writing class as an effort to assist them in writing a specific genre (Khansari et al, 2016), especially research articles.…”
Section: Pedagogical Implicationmentioning
confidence: 99%
“…In this light, prior research claims that rhetorical styles of particular genres are worth exploring in the English as Academic Purposes (EAP) class (Loi et al, 2015). It is also essential to introduce the concept of rhetorical styles in the academic writing class as an effort to assist them in writing a specific genre (Khansari et al, 2016), especially research articles.…”
Section: Pedagogical Implicationmentioning
confidence: 99%
“…There were other previous studies, whose findings were in accordance with this study finding which showed inclination of use 'Four-move model'. Those findings are such as the study of RA abstracts conducted by Tseng (2011) which analyzed ninety samples RA abstracts from three international journals, Wang and Tu (2014) whose corpus was thousand RA abstracts from four journals showing dominant use of 'Four move model' among others, and Khansari, D. et al (2016) mentioning that 'Four move model' (IMRD) followed international conventions which referred to (Swales, 1990), ISO 214 and suggested by American Psychological Association (2001).…”
Section: Tendency Of Rhetorical Move Usagementioning
confidence: 99%
“…Rhetorical move/step genre analyses of various texts have proliferated enormously. Several studies have investigated the generic move structure of RA abstracts in the following disciplines: linguistics (Zand-Vakili & Kashani 2012, Can et al 2016, Khansari et al 2016, literature (Tankó 2017), social sciences (Martıń 2003), accounting (Amnuai 2019), medicine (Salager-Meyer 1990), civil engineering (Kanoksilapatham 2013) and dentistry (Shamsabadi et al 2014, Vathanalaoha & Tangkiengsirisin 2018. Vathanalaoha and Tangkiengsirisin (2018) studied the move structure of Thai dental RA abstracts and international dental RA abstracts.…”
Section: Studies On Generic Structures Of Ra Abstractsmentioning
confidence: 99%